PRESPEKTIF KESETARAAN GENDER DALAM BUKU BAHASA ARAB MADRASAH IBTIDAIYAH - Luthfi Qolbi Azzahra; ⁠Muhajir; Ihda Auliya Ainul Jannah; Amy Fitriani Siregar (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2025)
The basis of this research is the importance of gender equality in the preparation of teaching materials, especially in textbooks used at the primary education level. Gender-biased textbooks can influence the way students view the social roles of men and women from an early age. This study aimed to identify and analyze gender bias and gender justice values contained in the Ministry of Religion's Arabic Language Student Book Class I MI 2020. This research is a literature study with a qualitative descriptive approach. The main data source comes from the Ministry of Religion's 2020 Arabic Student Book for Grade I MI. Data collection techniques were carried out through documentation and observation, while data analysis techniques used qualitative analysis. To ensure data validity, triangulation techniques were used. The results showed that there are still quite a lot of gender inequality in the book, including material that contains explicit examples of gender subordination. However, the book also contains some content that reflects the values of gender equality. The implication of this finding emphasizes the importance of the teacher's role in selecting and critically addressing learning content. Teachers are expected to be more vigilant and selective in using textbooks, and be able to provide students with a fair and equal understanding of gender roles in society.